Temperature Comparison of Denpasar City Land Surface before and during the Covid-19 Pandemic - Zulkarnain, Rizki Cholik (Bali Membangun Bali: Jurnal Bappeda Litbang, 2021)
Purpose: The purpose of this research was to look at the comparison of Ground Surface Temperature (LST) in Denpasar City before and during the Covid-19 pandemic. Research methods: To determine the LST used Landsat 8 image data which is processed using ArcGIS 10.3 software. Results and discussion: Limitation of community activities is carried out by the Denpasar City Government as an effort to reduce the spread of Covid-19. The decrease in anthropogenic activity due to restrictions on community activities during the Covid-19 pandemic affected the decrease in LST in Denpasar City. This is evident from the decrease in the average LST during the pandemic compared to the average LST before the Covid-19 pandemic. Implication: Government policies that impose restrictions on community activities have implications for decreasing anthropogenic activities. The increase or decrease in anthropogenic activity has an effect on the increase or decrease in LST in Denpasar City.